The effects of within-country linguistic and religious diversity on foreign acquisitions - Dow, Douglas; Cuypers, Ilya R P; Ertug, Gokhan (Journal of International Business Studies, 2016)
This article explores how within-country diversity of both language and religion influences the ownership structure of foreign acquisitions. Commentators have acknowledged the potential importance of “within-country diversity,” but to date this issue has received minimal empirical attention. We propose that diversity plays two distinct roles. Namely, diversity within the host country may be an additional source of behavioral uncertainty and information asymmetry, over and above the effects arising from cross-national differences. Moreover, diversity within the home country may increase the cognitive complexity of the decision makers, moderating the firm’s response to the distance and diversity of the host country. Results based on foreign acquisitions across 67 acquirer and 69 target countries confirm both of these roles. While the main focus of this article is on the role that within-country diversity plays in international business decisions, it also makes contributions in terms of expanding the range of dimensions of distance investigated in the cross-border acquisition literature, in highlighting a potentially positive role that diversity might play in such acquisitions, and in providing a potential explanation for asymmetries in distance – that is, differences in cognitive complexity.